Sex-dependent effects of multiple acute concurrent stresses on memory: a role for hippocampal estrogens - Hokenson, Rachael E.; Alam, Yasmine H.; Short, Annabel K.; Jung, Sunhee; Jang, Cholsoon; Baram, Tallie Z. (Frontiers in Behavioral Neuroscience, 2022)
Memory disruption commonly follows chronic stress, whereas acute stressors are generally benign. However, acute traumas such as mass shootings or natural disasters – lasting minutes to hours and consisting of simultaneous physical, social, and emotional stresses – are increasingly recognized as significant risk factors for memory problems and PTSD. Our prior work has revealed that these complex stresses (concurrent multiple acute stresses: MAS) disrupt hippocampus-dependent memory in male rodents. In females, the impacts of MAS are estrous cycle-dependent: MAS impair memory during early proestrus (high estrogens phase), whereas memory of female mice stressed during estrus (low estrogens phase) is protected. Female memory impairments limited to high estrogens phases suggests that higher levels of estrogens are necessary for MAS to disrupt memory, supported by evidence that males have higher hippocampal estradiol than estrous females. To test the role of estrogens in stress-induced memory deficits, we blocked estrogen production using aromatase inhibitors. A week of blockade protected male and female mice from MAS-induced memory disturbances, suggesting that high levels of estrogens are required for stress-provoked memory impairments in both males and females. To directly quantify 17β-estradiol in murine hippocampus we employed both ELISA and mass spectrometry, and identified significant confounders in both procedures. Taken together, the cross-cycle and aromatase studies in males and females support a role for high hippocampal estrogens in mediating the effect of complex acute stress on memory. Future studies focus on the receptors involved, the longevity of these effects, and their relation to PTSD-like behaviors in experimental models.